PENGARUH MODEL CPS BERBANTUAN MEDIA PAMFLET UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS V SD - Mardohar Hutapea, Levi Asi; Sihombing, Vania Rodearni; Pasaribu, Yusfi Laily; Syahrial, S (Universitas Negeri Medan, 2024)
To overcome the problem of lackof student participation in learning activities. Students find it difficult to develop theability to solve problems, especially indetermining and processing concepts and concepts. Obvious difficulties can be seen when the teacher gives students the opportunity to respond to the questions asked. Learning can be enhanced by either a system of student-centered learning, which will be able to improve students' creative thinking ability to learn and solve problems in everyday life, or teacher-centered learning, which will lead to more meaningful learning. This study aims to determine the effect of the pamphlet- assisted CPS model to improve the creative thinking skills of grade V students of SDN 104231 Batang Kuis. This research includes experimental research with the Quasi-Experimental method, where class V A as the experimental class will be treated and class V B as the control class that is not treated. The subjects in this study consisted of two classes, namely class V A which amounted to 40 students and class V B which amounted to 38. There are three data collection techniques in this study, namely questionnaires, observation sheets, and tests. In the pretest results, the experimental class got an average of 38.25 and the control class 36.84. Then the experimental class was given the CPS learning model treatment assisted by pamphlet media, while the control class was not given treatment. And the experimental class got a posttest result of 81.00 and the control class got an average score of 69.21. So it was concluded that there was an influence of the pamphlet media-assisted CPS model to improve students' creative thinking skills in theme 8 Our Friends Environment Subtheme 1 Human and Learning Environment 1 class V at SDN 104231 Dusun II, Sugiharjo, Batang Kuis District, Deli Serdang Regency, North Sumatra.Keywords: CPS, Pamphlet Media, Creative Thinking Skill